2010
DOI: 10.1590/s0037-86822010000600031
|View full text |Cite
|
Sign up to set email alerts
|

Neurological involvement in visceral leishmaniasis: case report

Abstract: Visceral leishmaniasis is a severe and potentially fatal vector-borne disease. The most typical symptoms are fever, hepatosplenomegaly, weight loss, bleeding and bacterial infections. Neurological changes are rarely reported. This paper describes a child who presented with neurological signs as the first symptoms of leishmaniasis; tone was diminished and tremors in the extremities were observed. A diagnosis of visceral leishmaniasis was confirmed by parasite detection in the bone marrow. Symptoms were reversed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
(13 reference statements)
0
10
0
4
Order By: Relevance
“…In Brazil, a case report showed that a child heavily parasitized by Leishmania presented neurological signs as the first symptoms of VL. This patient, presenting abnormal movements characterized by tremors in the hands and head, and myoclonic movements on his face, showed a diffuse reduction of the frontal lobes and cerebral atrophy in brain images analyses . Other few well‐documented reports refer mainly to meningoencephalitis and ocular manifestations .…”
Section: Neurological Alterations In Human Visceral Leishmaniasismentioning
confidence: 67%
“…In Brazil, a case report showed that a child heavily parasitized by Leishmania presented neurological signs as the first symptoms of VL. This patient, presenting abnormal movements characterized by tremors in the hands and head, and myoclonic movements on his face, showed a diffuse reduction of the frontal lobes and cerebral atrophy in brain images analyses . Other few well‐documented reports refer mainly to meningoencephalitis and ocular manifestations .…”
Section: Neurological Alterations In Human Visceral Leishmaniasismentioning
confidence: 67%
“…Sensorimotor peripheral neuropathy occurred in 46% of patients with leishmaniasis in one series [35]. Nerve biopsy in patients with Leishmania-associated neuropathy did not reveal inflammation or direct parasitic nerve involvement [35,36], although perineural Leishmania amastigotes and inflammation have rarely been identified in infected patients without signs or symptoms of neuropathy [37,38]. A predisposition to Leishmania-associated neuropathy in patients with concurrent vitamin deficiency has been debated [35].…”
Section: Leishmaniasis (Leishmania Species)mentioning
confidence: 99%
“…A leishmaniose visceral (LV) é transmitida ao homem por insetos vetores ou transmissores, conhecidos como flebotomíneos (Souto et al, 2013). A transmissão acontece quando uma fêmea infectada passa o protozoário a uma vítima sem a infecção, enquanto se alimenta de seu sangue (Diniz et al, 2010). É causada por espécies do gênero Leishmania, pertencentes ao complexo donovani.…”
Section: Introductionunclassified